Impact study of Chamravattom and Kootayi regulator cum bridges - JOMOL T. JOSEPH; Rasmina P; Remya V. Mohan; Dr. Abdul Hakkim V. M (Guide) (Tavanur 2014 Department of Land and Water Resources & Conservation Engineering)
Impact study of Chamravattom and Kootayi regulator cum bridges
Impact study of Chamravattom and Kootayi regulator cum bridges